Economic and Social Diversity in Australia's Cotton-producing Communities - Sorensen, Tony; Kotey, Bernice (Journal for Geography, 2009)
Australia’s highly profitable cotton industry is geographically constrained to districts in northern New South Wales and Southern Queensland. However, the rural towns servicing the industry are facing unprecedented stress on account of fierce commercial competition between them, many years of drought during the 2000s, technological innovation in cotton production, the chance occurrence of non-agricultural economic opportunities, and even ethnic composition. Our research focuses on the role of innovative small business in overcoming community stress and we have selected a small sample of six local government areas toexamine this link in depth. The selection of a representative sample entailed the classification of cotton communities on the basis of their economic and social profiles and how they had evolved over the inter-census period 2001-06. This analysis surprisingly showed that cotton growing regions are highly differentiated not just at a single point in time (2006), but also in their development trajectories. This considerably complicated the process of sample selection, but also demonstrated the diversity of rural settlement.